Kidney function and risk of cardiovascular disease and mortality in women: a prospective cohort study. (29th June 2009) - Kurth, Tobias; Jong, Paul E de; Cook, Nancy R; Buring, Julie E; Ridker, Paul M
Abstract : Objective To evaluate the association of kidney function with cardiovascular disease and mortality among apparently healthy women. Design Prospective cohort study. Setting Women's Health Study, United States. Participants 27 939 female health professionals aged ≥45 who were free of cardiovascular disease and other major disease and who provided a blood sample at study entry. Main outcome measures Time to cardiovascular disease (non-fatal stroke, non-fatal myocardial infarction, coronary revascularisation procedures, or death from cardiovascular cause), specific cardiovascular disease events, and all-cause mortality. End points were confirmed after review of medical records and death certificates. Results Glomerular filtration rate (GFR) was estimated with the abbreviated Modification of Diet in Renal Disease Study equation. At baseline, 1315 (4.7%) women had GFR <60 ml/min/1.73 m 2 . During 12 years of follow-up, 1199 incident cardiovascular disease events and 856 deaths (179 from cardiovascular disease) occurred. Compared with women with GFR ≥90 ml/min/1.73 m 2, the multivariable adjusted hazard ratios for any first cardiovascular disease were 0.95 (95% CI 0.83 to 1.08), 0.84 (0.70 to 1.00), and 1.00 (0.79 to 1.27) among women with GFR of 75-89.9, 60-74.9, and <60 ml/min/1.73 m 2, respectively; the equivalent hazard ratios for all cause mortality were 0.93 (0.79 to 1.09), 1.03 (0.85 to 1.26), and 1.09 (0.83 to 1.45). Similar null findings were observed for myocardial infarction, stroke, coronary revascularisation, and non-cardiovascular death. However, an increased risk of death from cardiovascular disease was found among women with GFR <60 ml/min/1.73 m 2 (hazard ratio 1.68 (1.02 to 2.79)). Conclusions In this large cohort of women, a glomerular filtration rate <60 ml/min/1.73 m 2 was associated with increased risk of cardiovascular disease death but not other cardiovascular disease events or non-cardiovascular disease mortality. We observed no increase in risk of any of the outcomes among women with less severe impairment of kidney function.